Legal Certainty for Banks in the Use of Power of Sale Related to Repossessed Assets - Gneissa Beltsazar; Nun Harrieti; Agus Suwandono (Journal of Law, Politic and Humanities, 2025)
Banks, as financial institutions, have an essential role in the economy, including in terms of providing credit. In the process of granting credit, collateral is one of the main elements that guarantee the debtor's ability to fulfil his obligations. One form of collateral that is often accepted is land rights, which are bound through mortgage rights based on Law Number 4 of 1996 concerning Mortgage Rights. This research aims to analyze the legal certainty related to the use of the power of sale by banks in relation to AYDA (repossessed collateral), as well as examine the legal aspects that need to be considered in its implementation. The research method used is a normative juridical approach, focusing on the analysis of relevant laws and regulations and related legal principles. The result of this research is that the position of a power of attorney to sell has a vital role in resolving bad debts, primarily related to the sale of collateral objects used as collateral in credit agreements. This power of attorney must meet the legal requirements of the contract stipulated in Article 1320 of the Civil Code and can take the form of a deed under the hand or an authentic deed. Legal certainty is critical in resolving bad debts through AYDA. The power of attorney to sell benefits the Bank by facilitating the execution of collateral, but it must also be balanced with strict supervision to avoid abuse of authority. This legal certainty also protects the rights of debtors, ensuring a transparent and fair process in the sale of assets. This increases public confidence in the banking system and provides protection for both parties. This research is expected to give a clearer understanding of the legality and legal implications of the use of a power of attorney to sell in the settlement of bad debts through AYDA.